Оптимизация структуры капитала как способ повышения стоимости предприятия (на примере ОАО «ТУРБОАТОМ») - Мищенко, Владимир Акимович; Чурсина, Т. Г. (НТУ "ХПИ", 2014)
В статье рассмотрен способ оптимизации структуры капитала предприятия и влияние данной структуры на стоимость компании в целом. Проведен анализ теоретических исследований в данной области. Рассмотрена деятельность отечественного гиганта машиностроения «Турбоатом». Исследование проведено за 5 лет деятельности предприятия и определена оптимальная структура капитала при которой стоимость предприятия максимальна. Данные выводы позволили дать прогнозы относительно финансовой деятельностиы предприятия в современных условиях.

The article describes a method for optimizing the capital structure of the company and the impact of this structure on the value of the company as a whole. The analysis of theoretical research in this area. Examined the activities of domestic engineering giant «Turboatom». The study was conducted over 5 years of the company and determined the optimal capital structure in which the maximum value of the enterprise. These findings allowed to give predictions about the financial activity of the enterprises in modern conditions.Theoretical questions of the capital structure in modern conditions of business administration. Analyzed the financial performance of large engineering enterprise in Ukraine for the past 5 years. The conclusions concerning the improvement of the overall financial stability vneschnem market.
Optimization of capital structure as a way to increase company value (based on the example of OJSC «Turboatom»)
Keywords: средневзвешенная стоимость капитала; инвестирование; рыночная стоимость; заёмный капитал; capital structure; company value; weighted average cost of capital; investments